S107 Treatment and outcomes for locally advanced (stage IIIA) lung cancer; 4 year experience from the National Lung Cancer Audit. (14th November 2013) - Woolhouse, I; Stanley, R; Callister, M; Barnard, S; Page, R; Beckett, P; Peake, Md
Abstract : Background: Surgery for lung cancer patients with mediastinal lymph node involvement (N2 disease) remains controversial. In one study (Albain 2009), progression-free (but not overall) survival was higher for patients who received induction chemo- radiotherapy followed by lobectomy but post operative mortality was high in pneumonectomy patients. We describe treatment and outcomes for patients with pre-treatment IIIA disease using data submitted from England to the National Lung Cancer Audit (NLCA) 2008–2011. Methods: Patients with pre-treatment staging of T1–3, N2, M0 were included. Small cell cancer, mesothelioma and carcinoid were excluded. The extent and histological nature of pre-treatment N2 disease is not recorded in the NLCA. Survival analyses were performed according to treatment received. Results: 6, 775 of 98, 403 (6.9%) patients met the inclusion criteria. 2, 669 (39%) patients had either chemotherapy or radiotherapy recorded and 2, 250 (33%) patients had no treatment recorded. 948 (14%) patients received chemotherapy and radiotherapy however radiotherapy treatment intent was recorded as curative in only 12%. 907 (13%) patients had surgery recorded as part of their treatment plan. Of these, 70% had post operative pathological nodal status recorded (25% N0, 14% N1, 30% N2). Median survival following surgery for the 271 patients with pathological N2 disease was 806 days, with 30 day survival of 99% and 1 year survival 76%. Conclusions: Lung cancer patients with stage IIIA disease make up a very small proportion of the overall lung cancer population. Only a small proportion of these patients receive surgery and there is significant discrepancy between the recorded pre and post operative nodal status. In patients with pathological confirmed N2 disease survival is similar to the 713 days reported in the Albain study. The automated collection of detailed radiotherapy/chemotherapy treatment data in future will allow a more reliable comparison between surgical and non-surgical treatments.